Evaluation of tensile bond strength of two different cements used for luting zirconia coping to one-piece zirconia implant - An in vitro study - Vishal Singh Bhadouria; Omkar Krishna Shetty; Reshu Sanan; Bhupender Kumar Yadav; Pankaj Kumar Ritwal; Kunal Nischal (Wolters Kluwer Medknow Publications, 2024)
Aim: The purpose of this in vitro study was the evaluation of the tensile bond strength of two different cements used for luting zirconia coping to one-piece zirconia implant. Settings and Design: The study was designed in an in vitro study setting. Materials and Methods: A one-piece zirconia implant was scanned on laboratory scanner, and thirty zirconia implants were milled by computer aided manufacturing (CAM). Subsequently, the abutment surface of each zirconia implants were scanned in laboratory scanner and coping with a hole was designed by computer-aided designing software, which was used for milling by computer-aided manufacturing (CAM). After various surface treatments of abutment and intaglio surface of coping, fifteen sets were cemented by glass ionomer cement (Group I) and the other fifteen sets by adhesive resin cement (Group II). All thirty samples after thermocycling were dried and pulled out in a universal testing machine, and tensile retention force is noted in pounds per square inch (psi). Statistical Analysis Used: Values for tensile retention force were tabulated for both the groups. Mean and standard deviation are calculated. Independent t-value and P value were calculated. Results: The least tensile retention force was reported in Group I (165.86 ± 25.74 psi). Maximum tensile retention force was received for Group II (396.81 ± 78.32 psi). Independent t-test was applied from which t-value calculated was 10.85 and P value obtained was 0.001, which means that there exists a very high difference in tensile bond strength of cement in Group I and Group II. Conclusions: Better tensile retention forces were observed in samples cemented with adhesive resin cement when compared to samples cemented with glass ionomer cement.